Patterns and Determinants of Intra-Industry Trade Between Indonesia and It's Trading Partner Countries - Nisa, Farah Choirun (Journal of Developing Economies, 2017)
This study discussed about the patterns and determinants that influenced the intra-industry trade between Indonesia and its trading partner countries, such as China, Japan, USA, South Korea and Singapore during 2004 to 2014. This study used an index of Grubel-Lloyd from four categories of manufacturing industry SITC 5-8 Rev. 3, 2 digits. In addition, this study also examined the determinants of IIT using panel data regression. Cross section in this study was between Indonesia with each trading partner countries (China, Japan, USA, South Korea and Singapore) and with its time series is 2004 to 2014. The results showed that IIT between Indonesia with each trading partner countries is high. Japan has the highest IIT among the other trading partner countries. The distance variable and the difference in GDP per capita did not affect the IIT. The average GDP variable has a positive and significant effect on the IIT, while the differences in value added per establishment at industry level has a negative effect on IIT. Keywords: Intra-Industry Trade, International Trade, Manufacture IndustryJEL: F14, L10